Pengaruh Dividend Payout Ratio dan Debt to Asset Ratio terhadap Price to Book Value pada PT Astra International Tbk - Fitriana Dewi Novianti Novianti; Benny Barnas; Djoni Djatnika (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This research was to know and analyze the effect of Dividend Payout Ratio and Debt to Asset Ratio on Price to Book Value. This study uses a quantitative descriptive method with reference to the financial statements of PT Astra International Tbk for the period 2014-2021. These financial reports are used as a source of obtaining data that will be processed into information in this research. The data analysis technique used multiple linear regression, classical assumption test, t test and F test. The results of the study partially Dividend Payout Ratio (DPR) has positive effect on Price to Book Value (PBV), while Debt to Asset Ratio (DAR) partially has a positive and significant effect on Price to Book Value (PBV). Simultaneously, Dividend Payout Ratio (DPR) and Debt to Asset Ratio (DAR) have a positive and significant effect on Price to Book Value (PBV)